ANALISIS PENGARUH SALES GROWTH, REO, SIZE, TATO, DAN CURRENT RATIO TERHADAP ROA DAN ROA TERHADAP BETA AKUNTANSI (ACCOUNTING BETA) (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2010-2014) - Nugraha, Pradifta Sulistya; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the influence of Sales Growth, Operating Efficiency Ratio (REO), Firm Size (Size), Total Asset Turnover (TATO), and Current Ratio (CR) towards Return On Assets (ROA) and Return On Assets (ROA) towards Accounting Beta. Sampling technique used in this paper is Purposive sampling with the criteria of Manufacturing Company that listed in Indonesia Stock Exchange (IDX) and period observation of 2010 to 2014, also the company has a complete financial statements data. The data used in this study is the annual report of the companies published by Indonesia Stock Exchange (IDX) with 38 samples of Manufacturing Company from a total of 200 Manufacturing Companies for 5 year long period of observation. The analysis used in this paper is multiple linear regression which tested by normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The analysis used in this paper is multiple linear regression with t test partial effect analysis, F test simultaneous analysis with the significance level of 5% and coefficient determination test. From the analysis, the first regression model showed that with the partial t test, Size, TATO, and Current Ratio has a positive significant effect on the company ROA for the period of 2010 to 2014 with the level of significance under 5%. Operation Efficiency Ratio (REO) partially has a negative significant effect on ROA. The Sales Growth variable, however showed that it has no significant effect on The Company's ROA. The simultaneous F test showed that Sales Growth, REO, Size, TATO and Current Ratio has a significant effect together for ROA with level of significance of 0,000. The second regression model showed that ROA has a positive significant effect on Accounting Beta with level of significance of 0,000 or under 5%.